Milk Production Advanced Genetic Traits, Cellular Mechanism, Animal Management and Health - Chaiyabutr, Narongsak (IntechOpen, 2012)
Book "Milk Production - Advanced Genetic Traits, Cellular Mechanism, Animal Nutrition and Management" is made for the publication of continuation of advances in the knowledge involving milk production. This book is divided into two main sections and is devoted to more specific consideration of areas with aspects of genetics factors and the molecular and cellular mechanisms, animal management, nutrition and husbandry. This book will be useful for students, researchers, teaching staff, practicing professionals connected with dairy science, animal science, food science, nutrition, physiology, biochemistry, veterinary medicine and other related fields. Each chapter in this book has an extensive bibliography which can future aid the reader in keeping abreast of the developments in this field.